2007
DOI: 10.1371/journal.pone.0001149
|View full text |Cite
|
Sign up to set email alerts
|

Common Human Cancer Genes Discovered by Integrated Gene-Expression Analysis

Abstract: BackgroundMicroarray technology enables a standardized, objective assessment of oncological diagnosis and prognosis. However, such studies are typically specific to certain cancer types, and the results have limited use due to inadequate validation in large patient cohorts. Discovery of genes commonly regulated in cancer may have an important implication in understanding the common molecular mechanism of cancer.Methods and FindingsWe described an integrated gene-expression analysis of 2,186 samples from 39 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 53 publications
1
53
0
Order By: Relevance
“…A plausible candidate that fits this criterion is the RORa1-binding site in the positive regulatory region of the LIMK2b promoter (Nomoto et al, 1999). In support, RORa mRNA is often downregulated in tumor cell lines and cancers (Zhu et al, 2006;Lu et al, 2007;Jetten 2009), and its expression is upregulated by a variety of genotoxic stresses (Zhu et al, 2006). Whether this latter function also includes coactivation with p53, for example, in the transactivation of LIMK2b, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible candidate that fits this criterion is the RORa1-binding site in the positive regulatory region of the LIMK2b promoter (Nomoto et al, 1999). In support, RORa mRNA is often downregulated in tumor cell lines and cancers (Zhu et al, 2006;Lu et al, 2007;Jetten 2009), and its expression is upregulated by a variety of genotoxic stresses (Zhu et al, 2006). Whether this latter function also includes coactivation with p53, for example, in the transactivation of LIMK2b, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…5 Microarray data sets collected from several studies have consistently shown most of the genes involved in glucose transport and glycolysis to be upregulated in different types of tumors. 9,16,17 Glucose transporters are overexpressed in hepatocarcinomas, breast cancer, neuroendocrine carcinomas, lymphoblastic leukemia and others. [18][19][20][21] It has been proposed that the high glucose uptake in cancer cells favors cell proliferation more than energy production because glucose metabolism mainly supports fatty acid and ribose-5-phosphate synthesis 5,22 ( Fig.…”
Section: Warburg Effect or Aerobic Glycolysismentioning
confidence: 99%
“…Glycolytic genes like TPI1, PGK1, ENOa, PK-M2, ALDO-A, GPI and PDHA1 were also found to be significantly upregulated in most of the 20 different types of common cancer examined, regardless of their tissue origin. 17 The substantial increase in the glycolytic flux of cancer cells is caused, in part, by the activation of the regulatory bi-functional 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB) enzyme. 23 Fructose-2,6-bisphosphate (F2,6BP) is synthesized by the PFKFB enzyme; F2,6BP is an allosteric activator of 6-phosphofructo-1-kinase (PFK-1), which is a rate-limiting enzyme that is an essential control point in the glycolytic pathway.…”
Section: Warburg Effect or Aerobic Glycolysismentioning
confidence: 99%
“…cancer cells. 53,54 Examination of GEO expression profiles 55 accession GSE3189 revealed that FBG1 is downregulated in melanomas. Fourth, this ubiquitin ligase degrades the adhesion receptor SHPS-1, which may be involved in tumor metastasis in melanomas and other cancers.…”
Section: Scf Ubiquitin Ligase Complex (Pdb Code 1ldk) Is Shown For Rementioning
confidence: 99%